Fitting logistic and autologistic models with autocorrelated errors using backfitting. ernadette Santos Fermin. - Fermin, Bernadette S. (University of the Philippines, 2001)
Abstract (Spatial and autocorrelation structures are hypothesized to be important components in addition to the hydrological variables to describe the state of an aquatic phenomenon indexed by a binary response variable. Two models that incorporate spatial and autocorrelation parameters to an ordinary logistic model (autologistics) are proposed in this study. The backfitting algorithm is applied to stiulated data so as to estimate the proposed models. The ordinary logistic model is used as a benchmark for comparison. The results indicate that the autologistic model is superior to the other two models in terms of its ability to classify binary events. Inclusion of the spatial parameter in a logistic model is a significant improvement in the prediction of binary events. Moreover, the backfitting algorithm converges faster using the autologistic model than the logistic model with spatial parameter).